Evidence-based principles of early diagnostics of carbohydrate metabolism disturbances in the internal disease practice - E. A. Poddubskaya; M. N. Mamedov (Кардиоваскулярная терапия и профилактика, 2012)
This review presents the World Health Organization (WHO) data on diabetes mellitus (DM) epidemiology, medical and social consequences, and economic losses due to DM complications. It is demonstrated that the diagnostics of early carbohydrate metabolism disturbances (ECMD) is an important component of Type 2 DM (DM-2) prevention. At the same time, it is known that ECMD are an independent risk factor of cardiovascular disease (CVD). At early stages of DM-2, metabolic disturbances precede first clinical manifestations of diabetes. The importance of early (preclinical) diagnostics of ECMD is emphasised. The authors present the results of meta-analyses and large studies on DM and prediabetes, which have clearly demonstrated that pathological hyperglycemia cannot be diagnosed based only on fasting glucose levels, as this would underestimate the actual prevalence of prediabetes. Relevant methods of early ECMD diagnostics are described.